Pengaruh Kepemimpinan Transformasional Dan Motivasi Kerja Terhadap Kinerja Karyawan - Adhie Fasha Nurhadian (Jurnal Ekonomi, Bisnis & Entrepreneurship, 2017)
This study aims to determine the effect of transformational leadership and motivation on employee performance either partially or simultaneously. The object of research is a company engaged in the field of financial services. Methods of survey research with inferential testing techniques using path analysis. Sampling technique uses census to all employees. The results showed that there is a significant influence of transformation leadership and motivation on employee performance either partially or simultaneously. Transformational leadership contributes 33.22%, while motivation contributes 28.95%, thus simultaneously the influence of transformational leadership and motivation on employee performance of 62.18%. These results indicate that the influence of these three variables is significant, while the rest is determined by other variables not examined in this study.